THE EFFECT OF COGNITIVE BEHAVIOUR THERAPY TO IMPROVE THE WELL-BEING OF PREGNANT WOMEN - Vijayalakshmi, P.; Subashini, R.; Anitha (International Journal of Psychosocial Rehabilitation, 2021)
Methods: Cognitive Behavioral Therapy (CBT) is a psychological intervention based on models of human behavior, cognition, and emotion. Of the 120 pregnant women who attended the counseling session, 58 were classified as having low well-being scores, while 62 had high scores. Out of the 58 with low well-being scores, 30 women were willing to participate and were selected as the sample. A scale was developed to measure perceived well-being, and its content validity was confirmed by experts in the field. The reliability of the scale was assessed through different methods: Cronbach’s alpha reliability was 0.59, the parallel form method had a reliability of 0.61, and the split-half method reliability was 0.62. Both English and Tamil versions of the questionnaire were used. The correlation coefficient of the scale was found to be 0.81. Results: The ’t’ value for the comparison was found to be 0.485 and 0.091, indicating no significant difference between the experimental and control group pre-test scores, and also no significant difference between pre-test and post-test scores in the control group. However, a paired sample t-test revealed a significant difference between pre-test scores (M = 181.13, SD = 13.789) and post-test scores (M = 196.24, SD = 16.835) for the experimental group. The control group had a mean pre-test score of 179.13 (SD = 14.015) and the experimental group’s post-test score was 196.27 (SD = 16.835) after the intervention. Conclusion: The results demonstrated a significant difference between pre-test and post-test scores in the experimental group. This suggests that CBT was effective in improving the perceived well-being of pregnant women, helping them manage physical and mental imbalances. The behavioral intervention program was shown to be beneficial for pregnant women.